Lavender Aromatherapy And Slow Deep Breathing In Hypertension Sleep Quality: Kombinasi Aromaterapi Lavender Dan Slow Deep Breathing Pada Kualitas Tidur Hipertensi - Nurotussaniah, Nadia; Sukesih, Sukesih; Indanah, Indanah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Hypertension is a major public health problem frequently accompanied by sleep quality disturbances that can worsen physiological and psychological conditions. Specific Background: Non-pharmacological approaches such as lavender aromatherapy and slow deep breathing are recognized as relaxation-based interventions that may support sleep regulation among hypertensive patients. Knowledge Gap: Previous studies have predominantly examined these interventions separately, while evidence on their combined application in rural community settings remains limited. Aims: This study aimed to examine the outcomes of combining lavender aromatherapy and slow deep breathing on sleep quality among patients with hypertension in Brakas Village. Results: Using a quasi-experimental control group pretest–posttest design, significant improvements in sleep quality scores were observed in the intervention group receiving both lavender aromatherapy and slow deep breathing, while the control group receiving slow deep breathing alone showed lower improvements, with statistically significant differences between groups (p < 0.001). Novelty: This study provides community-based evidence on the combined application of lavender aromatherapy and slow deep breathing among hypertensive patients in a rural setting. Implications: The findings indicate that this combined non-pharmacological approach may serve as a simple and practical option for improving sleep quality among people with hypertension at the community level. Highlights • Combination Intervention Produced Greater Sleep Quality Improvement• Community-Based Application In Rural Hypertension Patients• Non-Pharmacological Approach Using Relaxation-Based Methods Keywords Hypertension; Lavender Aromatherapy; Slow Deep Breathing; Sleep Quality; Non Pharmacological Therapy